Next generation sequencing shows diversity of Omicron sub-lineages of SARS-COV2 circulating in Jeddah, Saudi Arabia - Ahmed Bouna; Ahmed Atef; Hadiah Bassam Al-Mahdi; Ola H. Elgaddar; Mai M. Labib; Sherif Edris; Alawiah M. Alhebshi; Nahid H. Hajarah; Ahmed Bahieldin; Irfan A. Rather; Jamal S.M. Sabir (Journal of King Saud University: Science, 2024)
The ever-evolving Omicron variant of the SARS-CoV-2 and its sub-lineages have prompted Saudi Arabia to continuously track circulating lineages. We focused on the presence of diverse SARS-CoV-2 circulation in Saudi Arabia and presented the whole genome sequencing study of 94 positive SARS-CoV-2 specimens procured between February and April 2022 in the city of Jeddah, Saudi Arabia. Following whole-genome sequencing, bioinformatics analysis was undertaken. The SARS-CoV-2 variant Omicron clades 21K and 21L constituted the entirety of sequenced specimens, belonging to BA.2 (n = 56) and BA.1.1 (n = 20), respectively, and low-frequency sub-lineages were BA.2.3 (n = 6), BA.1 (n = 4), BA.2.40.1 (n = 2), BA.1.14 (n = 1), BA.2.10 (n = 1), BA2.32 (n = 1), BA.2.57 (n = 1), BA2.64 (n = 1), and BA2.5 (n = 1). Mutational patterns were identified, as well as possible consequences for the spread of the virus. Comparative molecular docking of Omicron-specific Nucleocapsid protein harboring the mutations P13L, R203K, G204R, as well as S413R, and the deletions E31-, R32-, and S33- showed reduced interaction with human RIG-I protein with 8 interacting amino acid residues and 10 polar interactions, while the SARS-CoV-2 Nucleocapsid protein exhibited 15 interacting amino acid residues and 26 polar interactions. Ongoing monitoring is essential for assessing the genomic epidemiological consequences of tourist travel and pilgrimage in Jeddah and across Saudi Arabia, as well as the prompt identification of emerging variants for further investigation.